2010
DOI: 10.1016/j.toxicon.2009.11.016
|View full text |Cite
|
Sign up to set email alerts
|

The anticancer effects of actinoporin RTX-A from the sea anemone Heteractis crispa (=Radianthus macrodactylus)

Abstract: Four isoforms of actinoporins were isolated in 2002-2004 from the tropical sea anemone Heteractis crispa (=Radianthus macrodactylus). Their potent hemolytic activities and effects on Ehrlich ascites carcinoma bearing mice were also studied. In this study, the individual actinoporin (RTX-A) demonstrated potential cancer-preventive activity at extremely low and non-cytotoxic concentrations. The substance suppressed the malignant transformation of mouse JB6 P + Cl41 cells stimulated by epidermal growth factor (EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 33 publications
3
41
0
Order By: Relevance
“…and C. sericeum showed both hemolytic and cytotoxic activities, and thus might have pore-forming cytolytic toxins such as actinoporins. An anticancer effect in a member of the actinoporins has been reported [31]. Thus, the hemolytic compounds from deep-sea jellyfish might have the potential for such a medicinal use.…”
Section: Discussionmentioning
confidence: 99%
“…and C. sericeum showed both hemolytic and cytotoxic activities, and thus might have pore-forming cytolytic toxins such as actinoporins. An anticancer effect in a member of the actinoporins has been reported [31]. Thus, the hemolytic compounds from deep-sea jellyfish might have the potential for such a medicinal use.…”
Section: Discussionmentioning
confidence: 99%
“…CI41 cells (Fedorov et al 2010). RTX-A toxin (H. crispa), induces P53-independent apoptosis and inhibits the activation of the oncogenic nuclear transcriptional factors AP-1 and NF-KB (Fedorov et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…CI41 cells (Fedorov et al 2010). RTX-A toxin (H. crispa), induces P53-independent apoptosis and inhibits the activation of the oncogenic nuclear transcriptional factors AP-1 and NF-KB (Fedorov et al 2010). The intrinsic and extrinsic apoptosis pathways converge with the activation of caspase-3 and subsequently other executioner caspases and nucleases drive the terminal events of programmed cell death (MacFarlane 2003;Crow et al 2004;Prunell et al 2005;Elmore 2007;Pizon et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies found that sea nettle nematocyst venom (SNV) peptide possessed significant antitumor effect on Ehrlich ascites carcinoma (EAC) tumor (Balamurugan et al, 2010). Four isoforms of actinoporin (RTX-A), isolated from the tropical sea anemone Heteractis crispa (=Radianthus macrodactylus), demonstrated potential cancer-preventive activity at extremely low and non-cytotoxic concentrations through the induction of p53-independent apoptosis and inhibition of the oncogenic AP-1 and NF-κB nuclear factors activity (Fedorov et al, 2010).…”
Section: Antitumor Activity Of Other Animal Toxinsmentioning
confidence: 99%